Comparison of the Effects of Rapid, Moderate, and Slow Weight Loss Combined with a Low-Calorie Diet and Physical Activity on Inflammatory Factors in Obese Women - Doroodian, Fatemeh; Luigi Bragazzi, Nicola (International Journal of Sport Studies for Health, 2025)
Objective: Obesity and overweight are defined as the excessive accumulation of fat in the body, which generally occurs when energy intake exceeds energy expenditure. Currently, obesity is considered one of the largest public health challenges worldwide and is inversely associated with various health outcomes. Obesity is often linked to inflammatory factors. The purpose of this study was to compare the effects of rapid, moderate, and slow weight loss combined with a low-calorie diet and physical activity on inflammatory markers in obese women.Methods and Materials: In this study, 36 obese women (ages 20 to 45 years) with a body mass index (BMI) of 30 or higher were randomly divided into three groups: rapid weight loss (combined training with 30-35% caloric deficit, 12 weeks, 12 participants), moderate weight loss (combined training with 20-25% caloric deficit, 10 weeks, 12 participants), and slow weight loss (combined training with 15-20% caloric deficit, 15 weeks, 12 participants). Participants underwent interventions for rapid, moderate, or slow weight loss, which included exercise and nutritional programs. Aerobic exercise consisted of walking and jogging on a treadmill at an intensity of 50-65% of maximum heart rate, and resistance training at 40% of one-repetition maximum (1RM), including dumbbell cross movements, biceps curls, and triceps extensions. Inflammatory markers, including Interleukin-1 (IL-1) and high-sensitivity C-reactive protein (hs-CRP), were measured at the beginning and end of the study. Data analysis was performed using ANOVA, Shapiro-Wilk, Levene's test, and covariance analysis. Statistical analyses were conducted using SPSS version 23 at a significance level of 0.05.Findings: Rapid, moderate, and slow weight loss combined with a low-calorie diet and physical activity did not have a significant effect on plasma IL-1 levels in obese women. However, significant differences were observed between the rapid weight loss group and the moderate and slow weight loss groups. Specifically, a 22.66% reduction in IL-1 levels was noted in the moderate weight loss group compared to the rapid weight loss group, and a 39.59% reduction was observed in the slow weight loss group compared to the rapid weight loss group. No significant difference was found between the moderate and slow weight loss groups. Similarly, rapid, moderate, and slow weight loss combined with a low-calorie diet and physical activity did not significantly affect plasma hs-CRP levels in obese women. However, a significant difference was observed between the rapid weight loss group and the slow weight loss group, with a 62.28% reduction in hs-CRP levels in the slow weight loss group compared to the rapid weight loss group. No significant differences were found between the other groups.Conclusion: Rapid, moderate, and slow weight loss combined with a low-calorie diet and physical activity does not significantly impact inflammatory factors.